Nanangenines: drimane sesquiterpenoids as the dominant metabolite cohort of a novel Australian fungus, Aspergillus nanangensis - Lacey, Heather J.; Gilchrist, Cameron L. M.; Crombie, Andrew; Kalaitzis, John A.; Vuong, Daniel; Rutledge, Peter J.; Turner, Peter; Pitt, John I.; Lacey, Ernest; Chooi, Yit-Heng; Piggott, Andrew M. (Beilstein Journal of Organic Chemistry, 2019)
Chemical investigation of an undescribed Australian fungus, Aspergillus nanangensis, led to the identification of the nanangenines – a family of seven new and three previously reported drimane sesquiterpenoids. The structures of the nanangenines were elucidated by detailed spectroscopic analysis supported by single crystal X-ray diffraction studies. The compounds were assayed for in vitro activity against bacteria, fungi, mammalian cells and plants. Bioinformatics analysis, including comparative analysis with other acyl drimenol-producing Aspergilli, led to the identification of a putative nanangenine biosynthetic gene cluster that corresponds to the proposed biosynthetic pathway for nanangenines.
Keywords: Aspergillus; biosynthesis; drimane; secondary metabolites; sesquiterpenoid; terpenes